The Influence Of Organizational Culture, Work Discipline, And Work Environment On Employee Performance At PT Bank Jatim Tbk Dr. Soetomo Surabaya Branch - Azarine Tahniah Setiawan; Acep Samsudin (International Journal of Social, Economic, and Business, 2025)
This study aims to analyze the influence of organizational culture, work discipline, and work environment on employee performance at PT Bank Jatim Dr. Soetomo Surabaya Branch. Human resources play a crucial role in organizational success, especially in the banking sector, which relies heavily on employee productivity and service quality. This research employs a quantitative method with a multiple linear regression approach. Data were collected through questionnaires distributed to employees and analyzed using SPSS Statistic 25 software. The results indicate that organizational culture, work discipline, and work environment have a significant simultaneous and partial impact on employee performance. The implications of this study emphasize the importance of companies in developing strategies to enhance organizational culture, work discipline, and work environment to ensure optimal and sustainable employee performance.